Global Trends and Future Outlooks in Centralized Exchange Research: A Comprehensive Bibliometric Review - Moch. Nuriko Firdaus; Ika Diyah Candra Arifah; Jorge Alberto Martinez Escandón (Universitas Negeri Surabaya, 2026)
Centralized exchanges (CEX) serve as the most widely adopted cryptocurrency trading platforms in Indonesia. However, research on this topic rarely positions Indonesia as the object of study. Therefore, this study analyzes the development and challenges of CEX through a systematic review supported by bibliometric analysis in order to map future research topics relevant to Indonesia. The literature search was conducted using the Scopus database with the following keywords: (